HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN MANAJEMEN SEKOLAH DENGAN EFEKTIFITAS KEPEMIMPINAN KEPALA SLTP SE-KABUPATEN KAMPAR - Gindo Mandalasa (Universitas Riau, 2017)
This study aims to determine the relationship between emotional intelligenceand school management individually or together with the effectiveness of the principal’s leadership.This research was conducted at Junior High School in Kampar Riau Regency, in 2003. Thesubjects were chosen based on random sampling technique with 74 head of junior high school.Meertage using Likert scale, with score range 1 to 4. Before the instrument used to capture thedata first used the trial in order to determine the feasibility test instrument. Validation by usinggrain analysis whereas its reliability is measured using Cronbach’s Alpa formula. Analyticaltechniques used are descriptive analysis, simple correlation, multiple correlation and partialcorrelation, with a significant level á = 0.05. These findings (1) there is a positive and significantrelationship between emotional intelligence (X1) with the effectiveness of leadership of theprincipal (Y). Is said to be significant because the increase of emotional intelligence score willbe minimized by the increase of leadership effectiveness score in the same direction (linearline) that is 0.66X1 with constant of 43.40 and positive because coefficient ry1 greater thanzero, that is 0.65 and expressed 42% The variation in the effectiveness of the principal’s leadershipis influenced by emotional intelligence (2) there is a positive relationship and the significationbetween school management (X2) and the effectiveness of principal leadership (Y), said to besignificant because the increase in school management score will be followed by increasedleadership effectiveness scores in the same direction (Linear line) equal to 0,492X2 with constant58,57 and is said positive because result of coefficient of ry2 bigger than zero is 0,786 andexpressed 62% variation of effectiveness of headmaster leadership influenced by schoolmanagement, (3) there is positive and significant correlation between intelligence Emotional(X1) and school management (X2) together Ma with the effectiveness of the principal’s leadership(Y). Due to the significant because there is a linear relationship that is the occurrence of eachincrease of a unity varial X1 and X2 will be followed by the increase of Y variable scores of0.28 and 0.39 in linear with the constant 41.81, said positive Karen ry12 greater than zero and82% Variations in the effectiveness of headmaster leadership can be explained jointly by emotionalintelligence and school management. Based on the findings, the researcher concludes that theeffectiveness of headmaster leadership can be improved through increased emotional intelligenceand school management application.